2022
DOI: 10.14716/ijtech.v13i4.4826
|View full text |Cite
|
Sign up to set email alerts
|

A Product Diffusion Model for the Extraction of Cerium and Yttrium from Magnetic Coal Fly Ash Using Citric Acid Solution

Abstract: The recovery of rare earth elements from coal-related materials, primarily fly ash, has become an emerging topic for the past few years. The availability of fly ash as solid waste from coal combustion and its low radionuclide concentrations benefit its utilization as an alternative source of rare earth elements. Using organic substances like citric acid to extract the elements further helps the environmental aspect. The maximum recovery value of cerium and yttrium was determined by reacting magnetic fly ash of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…These reserves must be utilized to meet domestic needs, where the REE industrial sector is projected to increase from USD 2,831 million in 2021 to USD 5,520.2 million in 2028 (Fortune Business Insight, 2021). In Indonesia, research regarding REE is carried out not only from Monazite and Xenotime but also from by-product raw materials such as Zircon tailings, as reported by Prameswara et al (2023) and Trisnawati et al (2020), it can also be found in coal-related by-products such as fly ash from coal combustion reported by Prihutami et al, 2021. Trisnawati et al (2020 reported that Y, Gd, Er, Dy, and Yb as HREEs2-(SO4)3 products can be recovered through sulfuric acid leaching, while the result from Prameswara et al (2023) showed that Dy and Yb leaching from solid REE-hydroxide using HCl solution afforded a total of 61.71% Dy and 74.55% Yb recovery.…”
Section: Introductionmentioning
confidence: 99%
“…These reserves must be utilized to meet domestic needs, where the REE industrial sector is projected to increase from USD 2,831 million in 2021 to USD 5,520.2 million in 2028 (Fortune Business Insight, 2021). In Indonesia, research regarding REE is carried out not only from Monazite and Xenotime but also from by-product raw materials such as Zircon tailings, as reported by Prameswara et al (2023) and Trisnawati et al (2020), it can also be found in coal-related by-products such as fly ash from coal combustion reported by Prihutami et al, 2021. Trisnawati et al (2020 reported that Y, Gd, Er, Dy, and Yb as HREEs2-(SO4)3 products can be recovered through sulfuric acid leaching, while the result from Prameswara et al (2023) showed that Dy and Yb leaching from solid REE-hydroxide using HCl solution afforded a total of 61.71% Dy and 74.55% Yb recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic knowledge aids in fundamental comprehension of the process, allowing for better process control and higher efficiency. Additionally, studying kinetics is crucial for scaling up the process, as noted by Prihutami et al (2021).…”
Section: Introductionmentioning
confidence: 99%